Causing the Breakdown of Family Life as Liability to Take Part in Withdrawal Treatment – In Light of Judicial Practice - Partyk, Aleksandra (Rodzina w systemie wsparcia i pomocy osobom z problemem alkoholowym, 2020)
The provisions of the Act of 26 October 1982 on Upbringing in Sobriety and Counteracting Alcoholism provide for the possibility of applying obligatory withdrawal treatment to an addicted person. Compulsory withdrawal treatment may be provided in a stationary or inpatient system. However, both forms of addiction treatment constitute a statutory exception, as withdrawal treatment is voluntary in principle. In particular, judicature points out that alcohol dependence alone is not sufficient to oblige a participant to undertake alcohol treatment. There must also be a so‑called social premise. One such premise is the fact that an addicted person is causing a breakdown of family life. In the jurisprudence of courts this circumstance is often referred to. However, whether this actually takes place is a matter of judgement. Not every conflict within a family constitutes a breakdown of family life. Moreover, the application cannot be taken into account if the family ties have already definitively disintegrated. At the same time, the court takes into account the state existing at the date of closing of the hearing, and therefore the improvement of the addicted person’s conduct, including the initiation of voluntary therapy, must influence the final direction of the court’s decision. A decision on the obligation to undertake alcohol treatment is particularly important if there is real fear that a crisis in a family affected by alcoholism of one of its members will deepen. Rapid reaction on the part of the state apparatus increases the probability of success.